The Effect of Oral Bromelain on Interleukin-6 Levels in Tissue of Acne Vulgaris Model Rats - Laura noviani; Muhammad Eko Irawanto; Endra Yustin Ellistasari; Arie Kusumawardani; Nurrachmat Mulianto (Journal of Social Research, 2026)
Acne vulgaris is a chronic inflammatory disorder of the pilosebaceous unit associated with Cutibacterium acnes colonization and activation of the Toll-like receptor–NF-?B pathway, which upregulates production of inflammatory mediators such as interleukin-6 (IL-6). Bromelain, a proteolytic enzyme derived from pineapple (Ananas comosus), is known to possess anti-inflammatory properties; however, experimental evidence regarding its effect on inflammatory cytokines in acne remains limited. This study aimed to evaluate the effect of oral bromelain administration on IL-6 levels in the tissue of acne vulgaris model rats. This in vivo laboratory experimental study employed a posttest-only control group design. Fifteen male Sprague-Dawley rats induced with C. acnes were divided into three groups: normal control (K1), negative control (K2), and treatment group (P) receiving oral bromelain at 88 mg/kgBW/day for 21 days. Tissue IL-6 levels were measured by enzyme-linked immunosorbent assay (ELISA). Data were analyzed using one-way ANOVA followed by a post hoc least significant difference (LSD) test. C. acnes induction significantly elevated tissue IL-6 levels compared to the normal control (p<0.001). One-way ANOVA revealed statistically significant differences in IL-6 levels between groups (p<0.001). The lowest IL-6 levels were observed in K1 (36.50±0.43) and the highest in K2 (94.01±0.57). The treatment group (P; 47.46±0.83) demonstrated significantly lower IL-6 levels than K2 and approximated K1 values. The post hoc LSD test confirmed statistically significant differences across all pairwise group comparisons (p<0.001). Oral bromelain administration effectively reduced IL-6 levels in the tissue of acne vulgaris model rats, demonstrating significant anti-inflammatory activity. These findings suggest that bromelain has potential as an adjunct therapy for inflammatory control in acne vulgaris.